What I Did Wrong - Weir, John (Fordham University Press, 2022)
Set in a rapidly gentrifying New York City determined to move beyond the decimation of a generation a decade earlier, What I Did Wrong is a day in the life of Tom, a forty-two-year-old English professor, haunted by the death of his best friend, Zack, who died theatrically and calamitously of AIDS. Tom himself slouches gingerly and precariously into middle age questioning every certainty he had about himself as a gay man while negotiating the field of his college classes, populated as they are with guys whose cocky bravado can’t quite compensate for their own confused masculinity. Tom tries to balance his awkwardly developing friendships with them. In the process, he begins to find common ground with these proud young men and, surprisingly, a way to claim his own place in the world, and in history.A powerfully moving—and often disarmingly funny—book about loss, character, and sexuality in the wake of AIDS, What I Did Wrong is a survivor’s tale in an age when all certainties have lost their logic and focus. It is a romance that embraces its objects from the traumas of toxic masculinity to the aftermath of catastrophic loss amidst the enduring allure of New York City in all its manic and heartbreaking grandeur